2013
DOI: 10.2337/diaclin.31.2.53
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Myonecrosis: An Indian Experience

Abstract: IN BRIEF Diabetic myonecrosis is an uncommon muscular complication of diabetes with significant morbidity. Clinical features and radiological findings are helpful in the diagnosis of myonecrosis. Management is conservative and focused on symptomatic relief and control of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…With resolution, the recurrence rate is approximately 40%. The long-term outcome tends to be poor due to five-year mortality from superimposed diabetic complications [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…With resolution, the recurrence rate is approximately 40%. The long-term outcome tends to be poor due to five-year mortality from superimposed diabetic complications [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another series by Gupta et al from an Indian centre, the mean (SD) age reported was 45.5 (7.3) years, the mean duration of diabetes was 9 years with an equal distribution of men and women and the mean (SD) HbA1c, 9.5% (0.6%) indicated poor glycaemic control at presentation with all the patients having concomitant one or more microvascular complications (Table II). [4][5][6][7] It being a rare disorder, the pathophysiology of this entity is unclear. Various hypotheses have postulated a complex interplay of atherosclerosis, microangiopathy, coagulopathy and ischaemia reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…1 resulting due to spontaneous ischemic necrosis of skeletal muscles. 2 It is one of the micro and macro-vascular complications of chronic diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%